Enhanced osteogenic differentiation of mesenchymal stem cells on poly(l‐lactide) nanofibrous scaffolds containing carbon nanomaterials. Issue 4 (2nd August 2014) - Duan, Shun; Yang, Xiaoping; Mei, Fang; Tang, Yan; Li, Xiaoli; Shi, Yuzhou; Mao, Jifu; Zhang, Hongquan; Cai, Qing
Abstract Carbon nanomaterials (CNMs), such as carbon nanotube (CNT) and graphene, are highlighted in bone regeneration because of their osteoinductive properties. Their combinations with nanofibrous polymeric scaffolds, which mimic the morphology of natural extracellular matrix of bone, arouse keen interest in bone tissue engineering. To this end, CNM were incorporated into nanofibrous poly(l‐lactic acid) scaffolds by thermal‐induced phase separation. The CNM‐containing composite nanofibrous scaffolds were biologically evaluated by both in vitro co‐culture of bone mesenchymal stem cells (BMSCs) and in vivo implantation. The nanofibrous structure itself demonstrated significant enhancement in cell adhesion, proliferation and oseogenic differentiation of BMSCs, and with the incorporation of CNM, the composite nanofibrous scaffolds further promoted osteogenic differentiation of BMSCs significantly. Between the two CNMs, graphene showed stronger effect in promoting osteogenic differentiation of BMSCs than CNT. The results of in vivo experiments revealed that the composite nanofibrous scaffolds had both good biocompatibility and strong ability in inducing osteogenesis. CNMs could remarkably enhance the expression of osteogenesis‐related proteins as well as the formation of type I collagen. Similarly, the graphene‐containing composite nanofibrous scaffolds demonstrated the strongest effect on inducing osteogenesis in vivo. These findings demonstrated that CNM‐containing composite nanofibrous scaffolds were obviously more efficient in promoting osteogenesis than pure polymeric scaffolds. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 103A: 1424–1435, 2015.